EFFECT OF HUMAN RESOURCE FLEXIBILITY IN PROMOTION INNOVATION PERFORMANCE - Assistant lecturer .Mohammad Ali Hussein Al- Saedi (Scholar Express Journals, 2023)
The current research aims to determine the effect of human resource flexibility as an independent variable on enhancing Innovation performance as a dependent variable. The Directorate of Education of The Governorate of Misan has been selected as a field of research, with the research community being one of the administrative leaders in the aforementioned directorate. A purposive sample of (38) staff members has been surveyed and analyzed using a questionnaire prepared for this purpose as a tool for collecting the necessary data. The dataset retrieved from the questionnaire was processed using statistical programs (spss V. 26) and Excel. The research has reached a number of conclusions, most notably: statistical results indicate that the research sample has the flexibility in its practice to adapt to the changing environment, in addition to constantly improving and changing practices in order to achieve the alignment of human resources with the changing system. The research yielded a number of recommendations, the most prominent of which is to strengthen cooperation and coordination between the Directorate of Education of Misan and its counterparts in other provinces. This is in order to benefit from the accumulated expertise of these directorates, whether in terms of preparing curricula and school plans, or in holding scientific conferences and seminars, in a way that contributes to the dissemination and sharing of knowledge among them. This is to enhance their creative behavior and thereby Innovation performance.
Keywords: Flexibility of human resources; Innovation performance